Model for Improving the Employee Productivity through Islamic Leadership and Internalization of Islamic Work Ethic in Sharia Tourism (Study on Sharia Hotels in Bandung) - Imas Soemaryani (Jurnal Bisnis Manajemen, 2018)
This research aims to describe the Islamic leadership and internalization of Islamic work ethic implemented in the sharia hotels. Besides, this research tries to explore the effect of Islamic leadership and Islamic work ethic on the employee productivity in the sharia hotels in Bandung. The unit of analysis and observation in this research are employees of sharia hotels in Bandung. The sample was taken using a simple random sampling method, and the data were processed using the Partial Least Square (PLS), expected to describe the effect between the variables and the degree of the manifest variable in constructing the latent variable within the limited observation unit. The results showed that the Islamic leadership and internalization of Islamic work ethic in the sharia hotels in Bandung are strong. The Islamic leadership and Islamic values positively affect the productivity of the employees.